2010
DOI: 10.1186/1477-7525-8-17
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported physical and mental health status and quality of life in adolescents: a latent variable mediation model

Abstract: BackgroundWe examined adolescents' differentiation of their self-reported physical and mental health status, the relative importance of these variables and five important life domains (satisfaction with family, friends, living environment, school and self) with respect to adolescents' global quality of life (QOL), and the extent to which the five life domains mediate the relationships between self-reported physical and mental health status and global QOL.MethodsThe data were obtained via a cross-sectional heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 65 publications
2
38
0
1
Order By: Relevance
“…In relation to one another, depressive symptoms were more strongly associated with self-reported mental health status, while PA was more strongly linked with self-reported physical health [30]. Perceived health incorporates physical, emotional and personal components of health that collectively make up individual “healthiness” ([14], p. 242).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to one another, depressive symptoms were more strongly associated with self-reported mental health status, while PA was more strongly linked with self-reported physical health [30]. Perceived health incorporates physical, emotional and personal components of health that collectively make up individual “healthiness” ([14], p. 242).…”
Section: Introductionmentioning
confidence: 99%
“…Sawatzky et al, 2010), this finding shows that being physically healthy promotes individuals' positive evaluations of their life. While this set of findings is consistent with what has been documented in the literature, the findings are unique in that the physical health benefits on psychological health and perceived life quality and satisfaction at Time 2 remained significant even after controlling for prior variance of the psychological wellbeing factors.…”
Section: Figurementioning
confidence: 69%
“…However, many of these studies relied on either a rather narrow conceptualisation of wellbeing and/or a limited scope of their measurement of wellbeing; for example, by operationalising sleep quality (Steptoe et al, 2008) or sleep duration (Hamilton et al, 2007) as physical wellbeing constructs, and by measuring psychological wellbeing with a global indicator (Nagyova et al, 2005), or a single item measure of mental and physical health (Sawatzky et al, 2010;see also Lyubbomirsky, King, & Diener, 2005, for a review). Moreover, most of these studies were conducted with general adult populations (see Bize et al, for a review), particularly adults with physical vulnerabilities, including people with chronic fatigue symptoms (Van Damme et al, 2006), spinal cord injury (Ginis et al, 2010), or rheumatoid arthritis (Nagyova et al, 2005).…”
Section: Gaps In the Research And Knowledge Basementioning
confidence: 98%
“…32 In a previous study investigating the contributions of mental and nutritional aspects to global QoL in adolescence, Sawatsky et al 33 found that 42% of the variance of global QoL scores was explained by satisfaction with self; 30% by mental health; 20% by satisfaction with family environment; 4% by satisfaction with living environment; 3% by physical health; and 0% by satisfaction with friendship. Although our theoretical and analytical approaches are somewhat different from those of the Sawatsky et al study, 33 on one hand, our results are in agreement with their findings about mental health and satisfaction with self as the variables that most account for variance in global QoL scores. On the other hand, our results suggested that peer relationships are an important factor for adolescent QoL.…”
Section: Discussionmentioning
confidence: 99%